2016
DOI: 10.1016/j.bbrc.2016.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod induces ER stress and Ca 2+ influx independently of TLR7 and TLR8

Abstract: Endoplasmic reticulum (ER) stress is a physiological response to protein overload or misfolded proteins in the ER. Certain anti-cancer drugs, e.g. bortezomib and nelfinavir, induce ER stress implying that this could be a successful therapeutic strategy against several forms of cancer. To find novel ER-stress inducers we screened a panel of natural and synthetic Toll-like receptor (TLR) agonists against human keratinocytes and identified the anti-cancer drug imiquimod (IMQ) as a potent inducer of ER stress. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…5). Recent evidence has shown that IMQ can still induce ER stress in mouse Tlr7 À/À cells [33]. Thus, in agreement with the above-mentioned report, our results demonstrate that IMQ induced ER stress independently of TLR7 and TLR8.…”
Section: Discussionsupporting
confidence: 93%
“…5). Recent evidence has shown that IMQ can still induce ER stress in mouse Tlr7 À/À cells [33]. Thus, in agreement with the above-mentioned report, our results demonstrate that IMQ induced ER stress independently of TLR7 and TLR8.…”
Section: Discussionsupporting
confidence: 93%
“…Although imiquimod is an agonist of TLR7, previous studies have shown that it can exert effects in tumour cells via TLR7-independent mechanisms [13, 18, 37, 38]. To determine whether this is the case in DFTD, we examined TLR7 expression in DFT1 and DFT2 cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Prostate cancer cells (PC3) were cultured in Roswell Park Memorial Institute (RPMI)-1640 medium with 10% fetal bovine serum (FBS) and 1% of 100 unit/mL of penicillin and streptomycin,20 and normal prostate cells (RWPE-1) were cultured in a concentration of 4×10 4 keratinocyte serum-free medium (K-SFM) supplemented with 0.2 ng/mL human epidermal growth factor (rhEGF) and 25 µg/mL bovine pituitary extract (BPE)21 and 1× antibiotic/antimycotic solution. Cultures were incubated at 37°C in a humidified atmosphere containing 5% CO 2 and passed weekly 2224…”
Section: Methodsmentioning
confidence: 99%